Perception of Residents about Coastal Tourism in the Municipality of Garopaba - SC: - Sperb, Matias Poli; Queiróz, Françoise da Silva (Revista Turismo em Análise, 2013)
This article presents the use of sustainable tourism indicators to verify in what degree the residents of Garopaba, SC, perceive sustainability or massification. These indicators are distributed in three large groups of subjects: job opportunities and economical aspects; local culture and quality of life; public administration and citizenship participation. The punctuation scheme, based on the frequency for variables of greater relevance, demonstrate how methodological triangulation can be an important strategy for crossing collected data by combining qualitative and quantitative data. Nevertheless, for greater accuracy and richness in results, the need for stratification of the sample by statistic software is observed. Key words: sustainable tourism indicators; methodological triangulation; key variables; stratification of the sample.